Energy diagnostics and forecasting the hokkey match of Russia and Germany team at XXIII Olympic Games in Pyeongchang - Sivakov, V. I.; Dolgova, V. I.; Komissarova, O. A.; Kamskova, Y. A.; Bacherikov , E. L.; Perepelyukova, E. V.; Cherkasov, I. F. (International Journal of Applied Exercise Physiology, 2019)
Purpose: analysis and justification of energy forms, content and forecasting the performance of hockey teams of Russia and Germany at the Olympic Games in Pyeongchang. Research methods: The quantum method is a contact or remote impact on the power system of hockey players, used for teams to diagnose, assess the restoration of the functional state during and after the game training and competitive load. Results: Analyzed and substantiated the energy law of productive game activity in the final game of the teams of Russia and Germany at the Olympic Games of the hockey match (02/25/2018). During the hockey match, the teams of Russia and Germany revealed a red, bright red, green-red, red-green energy in the form of a vertical, information square. The results of the study showed that the energy status of hockey players changes during the first, second and third periods in color form, content and this must be taken into account and efficiently manage not only the energy state, but also the functional state, sports result during the hockey match at the Olympic Games. Taking into account the energy status of the hockey team will contribute to high sporting achievements and prediction of the hockey match. Conclusion: The content and change of the color energy system of the hockey team indicates a high functional performance, athletic form and performs a high predictive function of the readiness of teams at the Olympic Games. The color energy information state of the hockey teams is the basis for predicting successful competitive activity.